2021
DOI: 10.1101/2021.02.08.430193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence for somatosensory attenuation during action observation of self-touch

Abstract: The discovery of mirror neurons in the macaque brain in the 1990s triggered investigations on putative human mirror neurons and their potential functionality. The leading proposed function has been action understanding: accordingly, we understand the actions of others by simulating them in our own motor system through a direct matching of the visual information to our own motor programs. Furthermore, it has been proposed that this simulation involves the prediction of the sensory consequences of the observed a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 98 publications
3
13
0
Order By: Relevance
“…First, previous studies have shown that double touch is not sufficient to produce somatosensory attenuation. For example, when both index fingers are simultaneously tapped (bimanual stimulation) in the absence of any movement ( 2 ) or in the presence of a passive movement ( 11 ), somatosensory attenuation does not occur. Similarly, when participants perform the force-matching task or the force discrimination task (as in the present study) and thus receive bimanual tactile stimulation, but a distance or a spatial mismatch is introduced between their hands/fingers, the attenuation is substantially reduced ( 7, 14, 112 ) or not present ( 6, 113 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, previous studies have shown that double touch is not sufficient to produce somatosensory attenuation. For example, when both index fingers are simultaneously tapped (bimanual stimulation) in the absence of any movement ( 2 ) or in the presence of a passive movement ( 11 ), somatosensory attenuation does not occur. Similarly, when participants perform the force-matching task or the force discrimination task (as in the present study) and thus receive bimanual tactile stimulation, but a distance or a spatial mismatch is introduced between their hands/fingers, the attenuation is substantially reduced ( 7, 14, 112 ) or not present ( 6, 113 ).…”
Section: Discussionmentioning
confidence: 99%
“…In all conditions, the comparison tap was delivered on the left index finger with a random delay of 800-1500 ms from the test tap. We opted to present the test tap before the comparison tap (fixed order design), consistent with previous studies ( 2, 4, 10, 11 ), to maintain the delay between the two taps constant across conditions and remove any effect of the comparison tap on the tap participants had to perform with their right index finger. For example, if the participants first received a 3 N comparison tap, they might press stronger to generate the subsequent test tap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychophysical paradigm was a two-alternative forced choice force-discrimination task that has been extensively used to assess somatosensory attenuation (Bays et al, 2006(Bays et al, , 2005Kilteni et al, 2021Kilteni et al, , 2020Kilteni et al, , 2019Kilteni and Ehrsson, 2020b). Participants sat comfortably on a chair and rested their left hand, palm up, with the left index finger placed inside a molded support (Figure 1).…”
Section: Psychophysical Taskmentioning
confidence: 99%
“…Moreover, the brain uses these predictions to attenuate the intensity of the self-generated signals, thereby amplifying the difference between self-generated and externally generated information (Bäß et al, 2008;Blakemore et al, 2000b;Gentsch and Schütz-Bosbach, 2011;Kilteni et al, 2020). In the tactile domain, this attenuation manifests in perceiving self-generated touch as being weaker than externally generated touch of the same intensity (Bays et al, 2005;Bays and Wolpert, 2008;Sarah Jayne Blakemore et al, 1999;Kilteni et al, 2021Kilteni et al, , 2020Kilteni et al, , 2018Kilteni and Ehrsson, 2020b, 2020a, 2017a, 2017bLalouni et al, 2020;Shergill et al, 2003) and in yielding weaker activity in the secondary somatosensory cortex and the cerebellum (Blakemore et al, 1998;Kilteni and Ehrsson, 2020a) and increased functional connectivity between the two areas (Kilteni and Ehrsson, 2020a). Somatosensory attenuation has been shown across a wide age range (18-88 years old) (Wolpe et al, 2016), and it is considered one of the reasons why we cannot tickle ourselves (Blakemore et al, 2000b;Leavens and Bard, 2016;Weiskrantz, L., Elliot, J.…”
Section: Introductionmentioning
confidence: 99%